LAND-SOIL CHARACTERISTICS FOR MAPPING PADDY CROPPING INTENSITY USING DECISION TREE ANALYSIS FROM SINGLE DATE ALI IMAGERY IN MAGELANG, CENTRAL JAVA, INDONESIA - Sanjiwana Arjasakusuma; Projo Danoedoro; Sigit Herumurti; Yanuar Adji Nugroho; Prama Ardha Aryaguna (Geoplanning: Journal of Geomatics and Planning, 2017)
Paddy field area and its cropping intensity are main information used to measure the crop production and the response of crop to changing climate conditions. Remote sensing technology has been used widely to map cropping pattern of paddy mostly using spectral analysis of multi temporal multispectral data of remote sensing. However, the cropping intensity of paddy was also influenced by the characteristics of planted land to paddy field which defines the level of land suitability for planting paddy.  This research aimed to map paddy rotation by using single date ALI imagery by assessing the land and soil characteristics based on the land suitability parameters for planting paddy.  Soil characteristics such as texture, acidity level, P205 (phosphor) and C-organic level collected from field work and terrain characteristics such as landform, surface water, and drainage density from visual delineation of SRTM 90 m was collected as inputs for the decision tree analysis to map the repetition of paddy planting throughout the year. The results showed the overall accuracy of 85% ± 8% (95 % level of confidence) for the final paddy rotation map where 2-times paddy per year was mostly found in the study area.